Bamboo-based composites: A review on fundamentals and processes of bamboo bonding. (15th April 2022) - Nkeuwa, William Nguegang; Zhang, Jialin; Semple, Kate E.; Chen, Meiling; Xia, Yeling; Dai, Chunping
Abstract: Sustainable development and applications of bamboo and bamboo-wood composites require better understanding and optimization of bamboo bonding. This paper provides a critical review of bamboo composite bonding in relation to wood bonding characteristics and processes. A polylamellate cell wall structure, low tissue porosity and permeability, and poor surface wettability hamper bamboo bonding with most wood adhesives. Bamboo element preparation, treatment and adhesive modification must be optimized in conjunction with more efficient material utilization and processes. Development of bond qualification standards similar to engineered wood products but tailored to stronger bamboo tissues are essential for structural bamboo composites. While phenolics are still commonly used for structural bamboo composite bonding, the industry is shifting away from formaldehyde systems. Isocyanate-based resins offer viable solutions, especially for bamboo strand composites. Changes in bamboo surface pH and wettability after industrial treatments like bleaching and pressure-steaming likely explain the variations in bonding performance with common wood adhesives. Hybrid bamboo-wood composites are promising cost-effective approaches for the engineered bamboo industry leading to viable building products. Future research subjects related to bamboo composite bonding are also discussed. Graphical abstract: Image 1 Highlights: Bamboo is difficult to bond due to its anatomic, physical and chemical attributes. Bleaching and plasma treatments improve bamboo wettability and bonding performance. Dual molecular weight phenol-formaldehyde adhesives are efficient for bonding bamboo. Combining bamboo and wood creates synergy for bonding and material properties.